1976
DOI: 10.1073/pnas.73.12.4584
|View full text |Cite
|
Sign up to set email alerts
|

Studies of human myasthenia gravis: electrophysiological and ultrastructural evidence compatible with antibody attachment to acetylcholine receptor complex.

Abstract: Neuromuscular junctions from patients with early onset and chronic myasthenia gravis were examined by electrophysiological and ultrastructural techniques. Acetylcholine (AcCh) sensitivities were reduced by 34-63% in early onset myasthenia and 60-80% in chronic myasthenia. Ultrastructural analysis revealed that virtually all junctional folds of the early onset patients were intact but that the AcCh-receptor-rich crests of these folds were uniformly covered by an attached layer of 30 X 70 A particles arranged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Alternatively, Patient IV was diagnosed as having both LES and myasthenia gravis (García et al, 1996). Thus, the effects of serum from Patient IV on muscle channels may be a consequence of neuromuscular inflammation by anti-AChR antibodies (Rash et al, 1976;Maselli et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Patient IV was diagnosed as having both LES and myasthenia gravis (García et al, 1996). Thus, the effects of serum from Patient IV on muscle channels may be a consequence of neuromuscular inflammation by anti-AChR antibodies (Rash et al, 1976;Maselli et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…patients. It has been suggested that the reduced ACh sensitivity in myasthenia gravis end-plates initially involves attachment of an anti-receptor antibody to one or more components of the acetylcholine receptors; indeed there is evidence for the presence of antibody in the synaptic cleft (Rash, Albuquerque, Hudson, Mayer & Satterfield, 1976;Engel et al 1977). Therefore, if an appreciable number of antibody-receptor complexes do remain present in the membrane, the antibody must be practically irreversibly attached to the receptor since no change in m.e.p.c.…”
Section: Resultsmentioning
confidence: 99%
“…As there is evidence for increased degradation of ACh-receptors at m.g. end-plates (Heinemann et al 1978; Reiness et al 1978) as well as destruction of junctional folds and lysis of the postsynaptic membrane (Rash et al 1976), these may be more important than reversible receptor block, in reducing post-synaptic ACh-sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been obtained in human myasthenia gravis (Elmqvist et at., 1964;Albuquerque et al, 1976;Rash et al, 1976) and in the chronic phase of experimental autoimmune myasthenia gravis in rats (Lambert et al, 1976 adding support to the concept of a postsynaptic defect in myasthenia gravis, which had earlier been proposed on the basis of a decreased number of bungarotoxin binding sites (Fambrough et al, 1973 (Lambert et al, 1976), or after passive transfer of serum from rats with the chronic form of this disease to normal recipient animals (Lindstrom et al, 1976a), the quantum content of EPPs and MEPP frequency are greatly reduced thus adding a presynaptic component to the transmission failure in these animals.…”
Section: Discussionmentioning
confidence: 99%